USER EXPERIENCE TEST OF FROG VIRTUAL LEARNING ENVIRONMENT WEBSITE (STUDENT MODULE) - Rahma Fitria (STMIK KAPUTAMA, 2022)
Education website is becoming popular to student in learning and accessing education materials. One of the education learning system adopted by Malaysia government which is Frog Virtual Learning Environment (VLE). This website has been used by all students around Malaysia. In order to have an effective learning environment during study, the website need to be tested by users to give feedbacks how the feel of the website after use. The purpose of this study is to perform user experience (UX) test on Frog Virtual Learning Environment (VLE). The UX test was conducted at computer laboratory of Sekolah Menengah Al Madrasah Al Alawiyah Ad Diniah Perlis with 6 students who have ever used the website rarely. During the test user was given several tasks regarding to the website while the facilitators conducted observation in order to analyze the usability metrics. The data gathered will reveal the strengths and weeknesses of the website. Usability Score is measured based on ISO usability metrics including effectiveness, efficiency and satisfaction. The result of this UX test revealed that the website is not user-friendly which has been proved by the usability score about 60% or below avarage. It is expected that this study could be adopted by software engineers or usability testers to produce a user-friendly education learning website that make students comfortable and easy to use the website.